Seric Musclin is not Increased in Patients with Metabolic Syndrome and Insulin Resistance (2018)
ABSTRACT: Skeletal muscle has now been recognized as an endocrine tissue, through the production and secretion of myokines. Musclin is a myokine mainly secreted by fibers type II (FT-II) that induces insulin resistance (IR) in both cellular and murine models. We hypothesize that musclin could be involved in pathophysiology of metabolic syndrome (MS) in humans. PURPOSE: to evaluate the relationships among IR, seric musclin, area occupied by FT-II and muscle mass in adults with and without MS. METHODS: analytical study in adults with and without MS. Homeostatic model assessment (HOMA-IR) was used as indicator of IR, musclin was measured by ELISA, area of FT-II in right vastus lateralis muscle by proton magnetic resonance spectroscopy and both fat and lean mass of the body and the right thigh (absolute values in Kg, or indexes in Kg/m2 and Kg/Kgbody mass) by dual X-ray absorptiometry. Data presented as mean±standard deviation. RESULTS: 23 subjects with and 10 without MS, comparable in age (51.6±5.7 with MS vs 53.5±6.3 without MS; P˃0.05) and gender were included. Subjects with MS had higher values of insulin (18.3±7.4 vs 6.7±2.5 μU/ml; P<0.05) and HOMA-IR (4.6±2.2 vs 1.6±0.6; P<0.05). There were no differences between groups regarding glycaemia (99.1±8.8 vs 93.2±12.7), musclin (609.9±203.4 pg ml-1 vs 657.9±240.5 pg ml-1), area of FT-II (51.4±23.2% vs 49±26.7%) or absolute values or indexes of muscle mass. There were positive correlations between HOMA-IR and both body fat mass or thigh fat mass (r˃0.46; P<0.05), between musclin and indexes of total lean mass (Kg m-2, r=0.51; P<0.05) and thigh lean mass (Kg m-2, r˃0.54; P<0.05), also between area of FT-II and indexes of total lean mass (r˃0.49; P<0.05). There was a negative trend between total lean mass and HOMA-IR (r=-0.34; P=0.07). We did not find correlation between HOMA- IR and musclin or area of FT-II. CONCLUSIONS: lean mass seems to determine seric musclin, however, this myokine was not associated to IR in our patients. These findings are in controversy with previous ones reported for cellular models.